VIRULENCE DIVERSITY OF RHIZOCTONIA SOLANI CAUSING SHEATH BLIGHT DISEASE IN RICE AND ITS HOST PATHOGEN INTERACTION - ADHIPATHI, PASUVARAJI; SINGH, VINEETA; CHAND MEENA, SURESH (The Bioscan, 2013)
The present investigation is carried out for the identification of resistant genotypes of rice against sheath blight disease and virulence diversity among the isolates of pathogen. This disease is caused by Rhizoctonia solani Kuhn (Teleomorph: Thanatephorus cucumeris) is one of the most ubiquitous and destructive soil borne disease. The 12 R. solani isolates were collected and characterized based on morphological and sclerotial characters and virulence diversity on 10 different rice varieties. The disease progress and severities were analysed using AUDPC value on the basis of lesion length recorded on 4, 8, 12 and 16 DAI. Evaluation on the basis of AUDPC value, out of 10 varieties of rice, Sarju-52 depicted highly resistant (19.91) while Jaya (21.87), UPR-2005-38 (23.97) and IET-15182 (23.16) showed moderately resistant disease reaction with most of the isolates tested; where as the variety Pusa Basmati-1 (46.57) depicted highly susceptible disease reaction. Among these some isolates were highly and moderately virulent whereas most of the isolates were less virulent. The identified resistant (Sarju-52) and susceptible (Pusa Basumati-1) is the potential source for the breeding programmes for further development of resistant varieties in rice.